Evaluating the effects of crystallinity in new biocompatible polyester nanocarriers on drug release behavior - Karavelidis V (Dove Medical Press, 2011)
Vassilios Karavelidis1,2, Evangelos Karavas2, Dimitrios Giliopoulos1, Sofia Papadimitriou1, Dimitrios Bikiaris11Laboratory of Polymer Chemistry and Technology, Chemistry Department, Aristotle University of Thessaloniki, Thessaloniki, 2Pharmathen SA, Pharmaceutical Industry, Pallini Attikis, Attiki, GreeceAbstract: Four new polyesters based on 1,3-propanediol and different aliphatic dicarboxylic acids were used to prepare ropinirole HCl-loaded nanoparticles. The novelty of this study lies in the use of polyesters with similar melting points but different degrees of crystallinity, varying from 29.8% to 67.5%, as drug nanocarriers. Based on their toxicity to human umbilical vein endothelial cells, these aliphatic polyesters were found to have cytotoxicity similar to that of polylactic acid and so may be considered as prominent drug nanocarriers. Drug encapsulation in polyesters was performed via an emulsification/solvent evaporation method. The mean particle size of drug-loaded nanoparticles was 164–228 nm, and the drug loading content was 16%–23%. Wide angle X-ray diffraction patterns showed that ropinirole HCl existed in an amorphous state within the nanoparticle polymer matrices. Drug release diagrams revealed a burst effect for ropinirole HCl in the first 6 hours, probably due to release of drug located on the nanoparticle surface, followed by slower release. The degree of crystallinity of the host polymer matrix seemed to be an important parameter, because higher drug release rates were observed in polyesters with a low degree of crystallinity.Keywords: biocompatible polyesters, nanoparticles, ropinirole, release, crystallinity